Use and Misuse of Russian Statistics - Gerschenkron, Alexander (The Review of Economics and Statistics, 1951)
THE preface by Marcelle Gaetan Pirou to Charles Bettelheim's L'Aconomie Sovietique ' announces that le lecteur sera certainement frappe de la sobriete et l'impartialite de ce volume. This reader feels that this prediction may have been too rash. If he was struck at all, it was by the light touch which distinguishes M. Bettelheim's treatment of statistical information and of problems of economic analysis. The long book is replete with statistical data copied from Soviet sources. At least in one case (p. 347) the figures given do not quite check with the source, but this reviewer does not wish to cast aspersion on M. Bettelheim's ability to copy accurately. What is wrong with the book is that the author hardly ever goes beyond the copying stage and does not try to understand the meaning of the figures he presents. Thus M. Bettelheim reprints the official series on grain crops, I928-40, without pointing out that the concept of the crop was changed in I933, and that the pre-i933 and the pOst-I933 portions of the series are not comparable without complicated adjustments; and he proceeds to interpret expressly the strong rise in output in I933 as an actual rather than a statistical increase (pp. 8I-82). In many cases (as, e.g., on pp. I5, I28, 298), the author presents ruble value figures without indicating whether they are expressed in constant or current prices. Foreign trade data are given in rubles but the rubles are not defined, and the reader is not forewarned that, while they have a definite relation to the dollar, they are unrelated to domestic rubles and that accordingly he must not try comparisons between, say, values of imports and values of industrial output. That grave problems are attached to the use of I926-27 prices as weights for the indices of industrial output seems unknown to the author. At one point (p. I36), there is indeed a veiled remark on certain modifications in statistical methods and a reference to a previous publication by the author; but that publication does not contain more than a passing reference to a rather secondary problem, viz., the treatment of outputs of small-scale industry. Meanwhile, the author discusses rates of industrial growth, productivity of labor, and comparisons with other countries without any concern for the upward bias in the Soviet index. As a result, the reader is left with altogether erroneous impressions. There are, however, at least two cases where the author goes a step beyond mere reproduction of Soviet data. In the first case, M. Bettelheim comes to the conclusion that between I928-29 and I937 real wages increased 25 per cent. How does he arrive at that result? He finds that the aggregate volume of agricultural goods and industrial consumers' goods increased 2.3 times between I928-29 and I937, while the value of goods sold in retail trade rose tenfold over the period. Therefrom the author deduces that retail prices must have increased about fourfold (I0:2.3). This is a bold deduction indeed, and the author mentions some of the uncertainties to which it is subject. He then compares the fourfold increase in prices with the development of average annual money wages and finds an increase by about five times. Hence his statement that real wages increased 25 per cent (5X4 . ioo). The troublesome fact, however, is that money wages did not rise fivefold over the period. M. Bettelheim is never too explicit about what he is doing. From the context, most readers will assume that his computations refer to wages in industry, for which a tabulation is given on page I84. If this is the case, then the fivefold increase results not from a comparison of 1937 and I928-29 (or rather I929), but from a comparison of the plan target for I942 with the figure for I929! If the period until I937 is taken, not a fivefold but about a threefold increase in money wages is shown, and accordingly the author would have to conclude that real wages fell more than 20 per cent (cf. 1 Charles Bettelheim, L'1conomie Sovie'tique. Published in the Gaetan Pirou's Series, Traits d'Aconomie politique (Recueil Sirey. Paris I95O). Vm. A72 nnp